Ethics in public health research: privacy and public health at risk: public health confidentiality in the digital age. - Myers J; Frieden TR; Bherwani KM; Henning KJ (American Journal of Public Health, 2008)
Public health agencies increasingly use electronic means to acquire, use, maintain, and store personal health information. Electronic data formats can improve performance of core public health functions, but potentially threaten privacy because they can be easily duplicated and transmitted to unauthorized people. Although such security breaches do occur, electronic data can be better secured than paper records, because authentication, authorization, auditing, and accountability can be facilitated. Public health professionals should collaborate with law and information technology colleagues to assess possible threats, implement updated policies, train staff, and develop preventive engineering measures to protect information. Tightened physical and electronic controls can prevent misuse of data, minimize the risk of security breaches, and help maintain the reputation and integrity of public health agencies.